ROLE PLAY TENTANG PENANGANAN SEDERHANA DAN BUTEYKO BREATHING PADA REMAJA MENDERITA ASTHMA RELAPSED DI MAN 2 KEDIRI - Widyasih Sunaringtyas; Ratna Hidayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
People with asthma may have initial or repeated attacks. The occurrence of re-attack or the occurrence of relapse can be experienced when in the school environment. Health care in schools involves the Red Cross.The knowledge and understanding of adolescents in schools is still very lacking, so education is needed. Education carried out in community service activities is carried out using the lecture method, interactive question and answer and role play.Community service activities are carried out in two stages, including the first stage, the speaker conveys to the selected Red Cross members for regeneration. Then the second stage of the selected Red Cross members educates other Red Cross members who are represented by two students or students in each class. This education aims to increase the knowledge of Red Cross members about the concept of asthma, simple handling and buteyko breathing in asthma. The target of the activity is Red Cross members totaling 40 people in MAN 2 Kediri.The evaluation of the success of the activities was carried out pre-test and post-test using questionnaires and observations, then analyzed using the Wilcoxon signed ranks statistical test. Based on the wilcoxon statistical test, the value of asymp sig 0.01 <0.05 H0 is rejected. Ha is accepted, it means that there is a difference in the average knowledge between pre and post education given the role play method. These results indicate a positive increase in 40 people experiencing an increase in knowledge. It is hoped that based on Red Cross members, they are able to provide simple treatment if there is a recurrence of asthma sufferers in the school environment.